CHILDREN’S DATA AND PRIVACY ONLINE- GROWING UP IN A DIGITAL AGE - Domazet, Siniša S; Šušak-Lozanovska, Ivona (The Policy of National Security, 2023)
In the digital era, there are countless security problems that juveniles are facing with, but privacy and data protection is one of the major challenges that needs to be solved by legislators. Research has shown that children’s rights, especially children’s privacy, are regulated by a large number of international regulations. At the European level, the right to privacy and the right to data protection are ensured both within the Council of Europe and within the European Union. The relevant legislation in the United States is the Children’s Online Privacy Protection Act, enforced by the Federal Trade Commission. It was determined that the most common violation of children’s data and privacy are online sharing, as well as Data Collection Practices of Mobile Applications. Children’s privacy on the Internet can be improved by better communication between parents and children regarding Internet use, educating children about cyber security and online threats, using parental control software, installing antivirus programs on devices used by children, and the like.